ANALISIS PEMANFAATAN DAN PEMELIHARAAN SARANA DAN PRASARANA PENDIDIKAN DI SEKOLAH DASAR NEGERI 2 SUKAGALIH C - Aliyah, Leli; S Putra , Karantiano; Sunarti Cikal Putri , Aulia; Aidah , Ai (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research examines the use and maintenance of educational facilities and infrastructure at SDN 2 SUKAGALIH. The focus of the research is how to use and maintain educational facilities. The aim of this research is to determine the use and maintenance of educational facilities. This research approach is qualitative with a descriptive type of approach. The data sources in this research are school principals, teachers and class teachers. Data collection techniques through observation, interviews and documentation. Data analysis through data reduction, data presentation and drawing conclusions. The results of the research and discussion can be concluded that: the educational facilities at SDN 2 SUKAGALIH have been utilized optimally, because; the teacher uses the class in accordance with the objectives achieved, the teacher teaches subject matter according to the media used, the teacher teaches students according to the material presented by utilizing the supporting facilities available at the school, and in the use of educational facilities must be considered in accordance with the character.different students. Meanwhile, maintenance of educational facilities at SDN 2 SUKAGALIH has been carried out optimally, where maintenance is seen in terms of nature in the form of checking, prevention, and minor and major repairs, and maintenance in terms of time, namely daily maintenance and periodic maintenance.